‘Wanting' and ‘Liking' Brain Mechanisms in Coaching: A qEEG Study using the CARE Coaching Model - Puspa, Lyra; Ibrahim, Nurhadi; Brown, Paul T. (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Coaching has become increasingly popular for leadership development and behavioral change in organizations. Recent studies suggest that motivation is essential in enhancing the effectiveness of workplace coaching. A number of studies revealed that delta and beta-gamma oscillations are associated with the human motivational process through ‘wanting' and ‘liking' mechanisms. However, the brain mechanisms of motivation in coaching have not been studied. This preliminary study is the first attempt to explore the ‘wanting' and ‘liking' mechanism of coaching, by investigating the activity of the delta and beta oscillations during a face-to-face coaching session through quantitative electroencephalogram (qEEG).Methods: Six male, right-handed, middle managers of an organization (mean age = 31.6) were recruited voluntarily as participants. A multichannel EEG (19 electrodes, 10/20 System) was used to record brain activity in both the resting state and the continuous 45-minute coaching session whilst using the CARE Model. The artifact-free EEG data were then quantified using wavelet analysis to obtain induced band power. Results: Significant increase was shown in delta and beta-gamma activities throughout the coaching session. Increased delta absolute power was found in the frontal, parietal, and occipital regions, whilst increased beta-gamma activity was significantly detected in the frontal, posterior temporal, and occipital regions. Conclusion: This preliminary result suggests that coaching, with regard to the CARE Model, induces both ‘wanting' and ‘liking' mechanisms simultaneously. Thus, the present findings provide the first preliminary neuroscientific underpinnings of the role of motivation in enhancing the effectiveness of workplace coaching through induced ‘wanting' and ‘liking' mental processes.